Considerations on Hispanic Sigillata in Italy - Martin, Archer (Rei Cretariae Romanae Fautorum Acta, 2022)
This paper collects published and unpublished Hispanic Sigillata found in Italy. Most of it comes from Ostia, although the ware is attested also at Rome and Ancona and has been reported from Elba. It consists largely of decorated vessels, for the most part Dragendorff 37 (with simple or almond rims). Alongside the dominant products from the Rioja, some pieces from Andújar are attested. Hispanic Sigillata is more than an anecdotal presence at Ostia – it belongs to a series of minor fine wares attested there in the late 1st and early 2nd centuries. It is also noteworthy that a fragment has been identified at Ancona.